2010
DOI: 10.1080/01932690903333044
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Dye-Polyether Derivatives as Dispersants for Its Parent Dye. Part 1: Synthesis and Hydrolysis Behavior

Abstract: A series of dye-polyether derivatives, supposedly to be used as dispersants for parent dye, were synthesized by grafting poly(oxyalkylene)-amines based on differing both molecular weights and degrees of hydrophilicity/hydrophobicity, onto C.I. disperse red 60 via a stable urea linkage. The structures of the dye-polyether derivatives were characterized by FTIR, 1 H NMR, and SEC. The influence of pH on the hydrolysis behaviors of the dye-polyether derivatives were studied in buffered aqueous solutions within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In view of the advantages of PEO–PPO block polymers, initially an attempt was made to use them as dye dispersants. To improve their affinity to the dye surface, in previous work a series of dye‐modified PEO–PPO polymers was synthesised with different molecular weights, in which the dye molecule (CI Disperse Red 60) was grafted onto polyether monoamines via a stable urea linkage . The application results showed that they had good dispersion efficiency with respect to their parent dye.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the advantages of PEO–PPO block polymers, initially an attempt was made to use them as dye dispersants. To improve their affinity to the dye surface, in previous work a series of dye‐modified PEO–PPO polymers was synthesised with different molecular weights, in which the dye molecule (CI Disperse Red 60) was grafted onto polyether monoamines via a stable urea linkage . The application results showed that they had good dispersion efficiency with respect to their parent dye.…”
Section: Introductionmentioning
confidence: 99%